Psikologi Pendidikan di Indonesia: Suatu Telaah Epistimologi - Nurhayani, Nurhayani (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
This article discusses the importance of epistemology in the development of educational psychology in Indonesia, considering the need for an educational approach that is rooted in the local context and at the same time meets global scientific standards. This study aims to understand how knowledge in educational psychology is constructed, validated, and developed through the perspective of the philosophy of science, and to identify the basic assumptions in the practice and theory of educational psychology that are developing in Indonesia. The method used is a systematic literature review of various relevant academic references, such as the work of Hanurawan (2012, 2019, 2020), Ghufron et al. (2013), Moore (2014), and Hofer & Pintrich (2002), with an analytical approach to the concepts of ontology, epistemology, and axiology in the context of educational psychology. The results of the review show that epistemology not only functions as a conceptual foundation in the development of theory, but also plays a central role in the validation of contextual and meaningful educational methods and practices. There is a significant transformation from the adoption of Western scientific methods to adaptations that take into account the socio-cultural realities of Indonesia, including the integration of Pancasila values ​​as the basic framework of local educational psychology. Epistemological understanding has been proven to improve the quality of learning, critical thinking of students, and the quality of teacher-student interactions. In addition, personal epistemology plays an important role in shaping students' beliefs about knowledge and the learning process. Thus, philosophical epistemology provides a more reflective and adaptive direction for the development of educational psychology in Indonesia as a contextual and transformative science.